Proteomic analysis shows that the main constituent of subepidermal localized cutaneous amyloidosis is not galectin-7. - Chapman, Jessica R (Amyloid, 2020)
Lichen or macular localized cutaneous amyloidoses have long been described as keratinic amyloidoses and believed to be due to the deposition of cytokeratin peptides originating from epidermis in the dermal papillae. However, recently it was suggested that galectin-7 is the causative protein for this type of amyloidosis. This was based on the detection of galectin-7 in a biopsy from a patient diagnosed with Bowen’s disease and localized cutaneous amyloidosis. In this study we report mass spectrometry-based proteomic analysis of the protein composition of localized cutaneous amyloid deposits from seven patients using laser microdissection and show that basal keratins are the main constituents of the amyloid deposits. Galectin-7 was not present in the dermal amyloid deposits and was only present in the overlying Congo red negative epidermis.